Middle East Monitor. The Gulf - Business Monitor International (London Business Monitor International, 2002)
BMI WP: ​Part of the Middle East and Africa Monitor series of newsletters, The Gulf Monitor provides a source of prime intelligence on Bahrain, Iran, Iraq, Kuwait, Oman, Qatar, Saudi Arabia, the United Arab Emirates and Yemen. It gives you advance warning of key changes in the business environment; regular appraisals of country risk; clear insights into economic and financial trends; and competitive intelligence on company and industry-wide developments and opportunities.
At head of title: MEM Only few issues of vols 12-13 and vols 17-18 are available at the library Related title: Middle East Monitor. East Med
Keywords: Economic conditions; ECONOMIC CONDITIONS; POLITICAL CONDITIONS; ECONOMIC FORECASTS; ARAB GULF STATES; MIDDLE EAST; PERIODICALS